Chitin-mediated plant–fungal interactions: catching, hiding and handshaking. (August 2015) - Shinya, Tomonori; Nakagawa, Tomomi; Kaku, Hanae; Shibuya, Naoto
Highlights: Plants recognize infecting fungi through the perception of released chitin fragments by LysM receptor complexes. Pathogenic fungi secrete effectors and change their cell walls to escape from the chitin-mediated immune system. Chitin-related molecules also serve as symbiotic signals in rhizobium/AM symbiosis. Dual function of OsCERK1 in both chitin-mediated immunity and AM symbiosis sheds a new light on the evolutionary relationships between these systems. Abstract : Plants can detect infecting fungi through the perception of chitin oligosaccharides by lysin motif receptors such as CEBiP and CERK1. A major function of CERK1 seems to be as a signaling molecule in the receptor complex formed with ligand-binding molecules and to activate downstream defense signaling. Fungal pathogens, however, have developed counter strategies to escape from the chitin-mediated detection by using effectors and/or changing their cell walls. Common structural features between chitin and Nod-/Myc-factors and corresponding receptors have suggested the close relationships between the chitin-mediated immunity and rhizobial/arbuscular mycorrhizal symbiosis. The recent discovery of the dual function of OsCERK1 in both plant immunity and mycorrhizal symbiosis sheds new light on the evolutionary relationships between defense and symbiotic systems in plants.